Cephalosporins Interfere With Quorum Sensing and Improve the Ability of Caenorhabditis elegans to Survive Pseudomonas aeruginosa Infection - Kumar, Lokender; Brenner, Nathanael; Brice, John; Klein-Seetharaman, Judith; Sarkar, Susanta K. (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa utilizes the quorum sensing (QS) system to strategically coordinate virulence and biofilm formation. Targeting QS pathways may be a potential anti-infective approach to treat P. aeruginosa infections. In the present study, we define cephalosporins' anti-QS activity using Chromobacterium violaceum CV026 for screening and QS-regulated mutants of P. aeruginosa for validation. We quantified the effects of three cephalosporins, cefepime, ceftazidime, and ceftriaxone, on 1) pyocyanin production using spectrophotometric assay, 2) bacterial motility using agar plate assay, and 3) biofilm formation using scanning electron microscopy. We also studied isogenic QS mutant strains of PAO1 (∆lasR, ∆rhlR, ∆pqsA, and ∆pqsR) to compare and distinguish QS-mediated effects on the motility phenotypes and bacterial growth with and without sub-MIC concentrations of antibiotics. Results showed that cephalosporins have anti-QS activity and reduce bacterial motility, pyocyanin production, and biofilm formation for CV026 and PAO1. Also, sub-MICs of cefepime increased aminoglycosides' antimicrobial activity against P. aeruginosa PAO1, suggesting the advantage of combined anti-QS and antibacterial treatment. To correlate experimentally observed anti-QS effects with the interactions between cephalosporins and QS receptors, we performed molecular docking with ligand binding sites of quorum sensing receptors using Autodock Vina. Molecular docking predicted cephalosporins' binding affinities to the ligand-binding pocket of QS receptors (CviR, LasR, and PqsR). To validate our results using an infection model, we quantified the survival rate of Caenorhabditis elegans following P. aeruginosa PAO1 challenge at concentrations less than the minimum inhibitory concentration (MIC) of antibiotics. C. elegans infected with PAO1 without antibiotics showed 0% survivability after 72 h. In contrast, PAO1-infected C. elegans showed 65±5%, 58±4%, and 49±8% survivability after treatment with cefepime, ceftazidime, and ceftriaxone, respectively. We determined the survival rates of C. elegans infected by QS mutant strains ∆lasR (32±11%), ∆rhlR (27±8%), ∆pqsA (27±10%), and ∆pqsR (37±6%), which suggest essential role of QS system in virulence. In summary, cephalosporins at sub-MIC concentrations show anti-QS activity and enhance the antibacterial efficacy of aminoglycosides, a different class of antibiotics. Thus, cephalosporins at sub-MIC concentrations in combination with other antibiotics are potential candidates for developing therapies to combat infections caused by P. aeruginosa.